Experimental demonstration of square Fresnel zone plate with chiral side lobes - Vijayakumar A.; Vinoth B.; Minin I. V. Igor Vladilenovich; Rosen J. Joseph; Minin O. V. Oleg Vladilenovich; Chau-Jern Cheng (2017, 2017)
Title screen